Warranties arising from procedural rules and european jurisprudence in administrative order - Olivier Gohin (Zbornik Radova Pravnog Fakulteta u Splitu, 2013)
Amongst the rules applicable in administrative dispute, those created from the European Convention for Human Rights and Fundamental Freedoms should particularly be emphasised. Similarly, administrative adjudication has accepted, after the Council of State’s decision on October 20, 1989 in the Nicolo case, to supervise harmonisation of national law and a certain agreement, namely the European Union Association Agreement. This has resulted in self interpretation of the agreement. In resolving various issues, the administrative judge was forced to follow Strasbourg court practice. Therefore, finally, as a logical conclusion, the question arises of: Is national law being europeanised or is European law becoming “nationalised?”